Reflecting on reflecting in the study of contemporary pagan and magical ritual - Velkoborská, Kamila (Religio, 2014)
Reflexivity, once a revolutionary idea and now an established dogma, can become a vital tool in anthropological fieldwork only provided that it is considered in its complexity and not simply as being conscious of the self. Such a tool is especially important in research conducted in the area of lived religion, which requires intellectual and emotional commitment on the part of the researcher and has, therefore, a possible impact on the researcher's life beyond the time-space of the research proper. Drawing on my longitudinal fieldwork and my participant observations among contemporary pagans and witches in order to demonstrate this point, I selected mainly examples of situations that can be seen as endangering the quality of the research due to the fact that they are connected with the researcher's personal propensities and emotional setup and therefore difficult to control. The goal of the article is to show how reflexivity, combined with a multi-site research strategy, can effectively deal with such situations and help the researcher produce ethnographic writing which reflects both the outlook of the insider fully engaged in the processes played out in the field and the perspective of the outsider observing the processes as if from a distance, including those going on in his or her head.